Crack Propagation Analysis of Magnesium Rod Processed by Extrusion-shear: Numerical Modeling and Experimental Verification - Hu,Hong Jun (2015)
During extrusion-shear (ES) process, the surface cracks would be formed in the processed rod for AZ31 magnesium caused by nonhomogeneous metal flow and stress. To reduce the cracks defects, three-dimensional (3D) finite element method (FEM) of ES on a wrought AZ31 magnesium alloy have been performed. ES process experiments have been also conducted to verify the simulation results under the identical conditions. It can be found that the tendency to generate the dead zone is decreased by employing the ES die with the extrusion ratio of 28 comparing to the one with the extrusion ratio of 11.6. With the extrusion ratio 28, the surface stresses of the rod at the die exit are decreased greatly so that the surface cracks are avoided. The ES die with the extrusion ratio of 28 would increase temperature on the rod surface and subsequently result in the sacrifice of the tensile strength of the AZ31 rod. Damage model has been chosen and Cockcroft–Latham damage factor has been set and incorporated into DEFORM software. The simulation results show that the larger extrusion ratio would have the smaller crack propagation. Experimental validation shows that the results of experiments are in accordance with those from computer simulation. The study indicates that FEM can be used confidently for designing ES dies and process parameters in CAE environment for DEFORM software to improve the product quality and productivity by avoiding trail runs.